The distribution network voltage in the presence of distributed generation / Mohd Firdaus Shaari - Shaari, Mohd Firdaus (2007)
This paper presents voltage stability studies in the presence of distributed generation. In this study, the voltage study analysis in transient mode will be performed with and without the presence of distributed generator. The effect of distribution generator will also be investigated. Several simulation models will be developed for the implementation of the study. A simple test system will be utilized for this study